The Rightsizing Strategies of Chinese SMEs During the Global Economic Downturn: Exploring the Influence of Family Ownership - Lad, Amit (2009)
Over the last two decades China has risen to become one the biggest economic powers in the world. A large proportion of the growth experienced in this region has been attributed to a strong manufacturing sector and a high volume of exports, in particular, to the west. However, over the past one and a half years the world has experienced one of the worst economic downturns ever seen and export led economies such as China have felt the repercussions of this slump. Small and medium-sized enterprises (SMEs) have been most affected and many have failed to survive. As a result SMEs have had to adopt effective rightsizing strategies in order to promote their survival through the harsh business environment. Using a sample of SMEs in Zhejiang Province, China, this paper aimed to explore the rightsizing strategies used by Chinese SMEs as a result of the worsening economic conditions to promote survival. Analysis of survey data indicated that Chinese SMEs were adopting a range of rightsizing strategies in order to maintain operations. Evidence showed that Chinese SMEs tended to avoid using strategies to cut salary expenditures and also avoid reducing their number of full-time workers. Proactive strategies were more common among the SMEs in this study. Many of the firms had committed to hiring more skilled workers and firms were also increasing research and development expenditure. This study also aimed to explore the influence of family ownership upon the rightsizing strategies used but Chinese SMEs. Family ownership was found to have a significant effect on some of the rightsizing strategies used by the SMEs in this study. In particular, family owned SMEs were significantly less likely to adopt salary expenditure reduction strategies compared with non-family owned SMEs. Family businesses were also more likely to avoid using layoffs in favour of other strategies, highlighting the paternalistic and altruistic nature of these firms.